Criteria for the definition of Pituitary Tumor Centers of Excellence (PTCOE): A Pituitary Society Statement - Casanueva, Felipe F.; Barkan, Ariel L.; Buchfelder, Michael; Klibanski, Anne; Laws, Edward R.; Loeffler, Jay S.; Melmed, Shlomo; Mortini, Pietro; Wass, John; Giustina, Andrea (Pituitary, 2017)
INTRODUCTION: With the goal of generate uniform criteria among centers dealing with pituitary tumors and to enhance patient care, the Pituitary Society decided to generate criteria for developing Pituitary Tumors Centers of Excellence (PTCOE). METHODS: To develop that task, a group of ten experts served as a Task Force and through two years of iterative work an initial draft was elaborated. This draft was discussed, modified and finally approved by the Board of Directors of the Pituitary Society. Such document was presented and debated at a specific session of the Congress of the Pituitary Society, Orlando 2017, and suggestions were incorporated. Finally the document was distributed to a large group of global experts that introduced further modifications with final endorsement. RESULTS: After five years of iterative work a document with the ideal criteria for a PTCOE is presented. CONCLUSIONS: Acknowledging that very few centers in the world, if any, likely fulfill the requirements here presented, the document may be a tool to guide improvements of care delivery to patients with pituitary disorders. All these criteria must be accommodated to the regulations and organization of Health of a given country.
EVALuna2:102196